(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Phytochemical analysis using GC-MS is a novel approach in analysis of bioactive compounds in plant materials. The study was carried out with the objective of investigating the phytochemical constituents of leaves extracts of Henna and Bitter melon using GC-MS analysis to identified the bioactive compounds there in. The plant materials were obtained in Maiduguri Metropolitan Council (MMC) in March 2024, air dried in shade for two days and pulverized into fine powder, 100g of each of the plants powder was dissolved in methanol to obtain the extract. An aliquot of the extracts of Henna and Bitter melon were then divided into two part. One part was used for phytochemical analysis while the second part use in the GC-MS analysis. Results for the phytochemical analysis indicate the presence of eight phytochemical compounds in Henna, they includes the following; Flavonoid, Tannins, Saponin, Alkaloids, Glycosides, Anthraquinones, Phenols and Steroids while Bitter melon had six phytochemical compounds; Flavonoid, Tannins, Saponin, Alkaloids, Anthraquinones and Phenols. The GC-MS analysis indicate the presence of 14 bioactive compounds in each of the leaves samples of Henna and Bitter melon identified to have antimicrobial activity. It can be concluded that both Henna and Bitter melon could be used effectively in the integrated management of plant diseases in the study area as both plants are readily available, safe, cheap and easy to obtained.